Differences in the induction of induced human CD4+ CD25+ FoxP3+ T-regulatory cells and CD3+ CD8+ CD28− T-suppressor cells subset phenotypes in vitro: comparison of phorbol 12-myristate 13-acetate/ionomycin and phytohemagglutinin stimulation - Wang, Haihao; Daniel, Volker; Sadeghi, Mahmoud; Opelz, Gerhard (Transplantation proceedings, 2013)
CD4+ CD25+ FoxP3+ T-regulatory cells (Treg) and CD3+ CD8+ CD28− T-suppressor cells (Ts) were shown to have immunosuppressive function in vivo and in vitro. However, the in vitro inducibility of Ts subsets is rather unclear. We investigated the induction of Treg and Ts subsets in peripheral blood mononuclear cells of 5 healthy control individuals during stimulation with phorbol 12-myristate 13-acetate (PMA)/ionomycin or phytohemagglutinin (PHA). Phenotypes were analyzed 0, 4, 8, 16, and 24 hours after initiation of cell culture using 4-color fluorescence flow-cytometry. Number of CD4+ CD25+ FoxP3+ CD127− Treg increased during PMA/ionomycin or PHA stimulation (P < .01). CD4+ CD25+ FoxP3+ Treg coexpressed the phenotypes interleukin (IL)-2−, IL-10+, and/or transforming growth factor (TGF)-β+ after stimulation (all P < .01). Interferon (IFN)-γ production was induced only by PMA/ionomycin (P < .01) but not by PHA (P = NS). IFN-γ-secreting Treg were detectable at 4 hours whereas IL-2−, IL-10+ and/or TGF-β+ Treg required 16 hours of stimulation. In contrast, CD3+ CD8+ CD28− Ts phenotypes were not inducible during 24-hour PMA/ionomycin or PHA stimulation (all P = NS). However, Ts coexpressed IL-10 and/or TGF-β during polyclonal stimulation (all P < .01), whereas the proportion of IL-2− Ts remained stable during the cell culture period (P = NS). Similar to Treg, IFN-γ-secreting Ts were detected only during PMA/ionomycin stimulation (P < .01), but not during PHA stimulation (P = NS). We conclude that the proportion of CD3+ CD8+ CD28− Ts remains stable during polyclonal stimulation. They modify only the cytokine pattern indicating activation of the Ts. In contrast, CD4+ CD25+ FoxP3+ CD127− Treg are inducible by PMA/ionomycin and PHA stimulation. IFN-γ- secreting Treg form the first line of immunoregulatory T cells during an initiated immune response followed by IL-2−, IL-10+, and/or TGF-β+ Treg.